(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
Soil fertility reduction is the main problem for sustainable crop production and productivity in southern parts of Ethiopia. Integrated soil fertility management is the best choice to improve soil fertility constraints using accessible organic and chemical fertilizers. The aim of the experiment was to examine the effect of organic and chemical fertilizers on crop yield and soil fertility improvement. This experiment was conducted from 2017 to 2018 in Debub Ari district, southwestern Ethiopia. The treatments contain Control (no fertilizers), Recommended NP (69/30), 250 kg NPSB + 161 kg ha-1 Urea, 10 t ha-1 compost, and 5 t ha-1 compost + 125 kg NPSB + 80 kg Urea top dress. Potato variety ‘Belete’ became used for the experiment and was planted early in the ‘Belg’ season. The treatments were arranged in randomized complete block design with three replications. Soil sample was randomly collected before treatment application with a depth of (0-20cm) and composited into one kg of a sample. The analysis results of the initial soil sample revealed that it was sandy clay in texture, moderately acidic, low in total N, OC, CEC, and very low in available P. The analysis of variances showed significant differences among the treatments on potato tuber yield when compared to untreated plots. Potato tuber yield is increased by 32, 22, and 35% of sole use of inorganic fertilizer, compost alone, and 50% of compost + 50% of NPSB treatment, respectively, than control. The maximum tuber yield 18.7 t ha-1 was obtained from treatment 5 t ha-1 compost + 125 kg NPSB + 80 kg Urea top dress, whereas the minimum tuber yields 13.85 t ha-1 were obtained by untreated plot (without any fertilizer application). Farmers in the study area can use by selecting either recommended NP (69 N and 30 P) ha-1 or 5t + 125 kg NPSB + 80 kg urea ha-1 depending on the accessibility of labor, composting material, and cash to purchase an adequate amount of fertilizers. Int. J. Agril. Res. Innov. Tech. 13(1): 77-82, June 2023